Peran Guru IPS Dalam Membentuk Karakter Peduli Lingkungan Melalui Program Adiwiyata Di SMPN 1 Wlingi - Fadia Hayya Kurnia; Hendra Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
Teachers are a big influence in cultivating the success of students' insight and attitudes. The guidance given by teachers also needs to be given to the values of caring for the environment. The character of caring for the environment does not only come from intuition and talent, but also comes from habits and an educational process that cares about the environment. A concrete manifestation provided by the government in cultivating the character of caring for the environment through the Adiwiyata Program in schools. The predicate of Adiwiyata is Mandiri and is an example of a school to be coached by other schools, so to find out more the researcher wants to conduct research on the role of teachers in cultivating environmentally caring character through the Adiwiyata program. The aim of this research is to (1) find out the role of social studies teachers in forming character caring for the environment at SMPN 1 Wlingi (2) knowing the form of character that cares for the environment in students at SMPN 1 Wlingi. This research uses a qualitative approach and an intrinsic case study type of research. Data collection techniques through observation, interviews and documentation. Checking data validity through technical triangulation and confirmability. The data analysis technique for this research is the Miles and Huberman technique through data reduction, data presentation, drawing conclusions. The results of this research are 1) The Role of Social Studies Teachers in Forming Environmentally Caring Characters a) Curriculum that is integrated with the environment, in the form of lesson plans/teaching modules that are integrated with material about the environment b) Participatory activities, in the form of the habit of cleaning the environment every morning, with guidance teachers, and insight through activities from learning materials. 2) Forming environmentally caring character through the Adiwiyata Program at SMPN 1 Wlingi in the form of an independent attitude and sense of responsibility possessed by students which is proven by the many activities that support the Adiwiyata Program, such as picket activities every morning and after school, clean Fridays, competitions cleanliness of the class, several activities integrated with learning materials in the form of making vlogs. and in general, SMPN 1 Wlingi implements minimizing plastic waste through the attitude of students by bringing provisions or drink bottles from home.